2019–2020 Florida Citrus Production Guide: Pesticides Registered for Use on Florida Citrus - Lauren M. Diepenbrock; Megan M. Dewdney; Tripti Vashisth; Stephen H. Futch (EDIS)
This 40-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. It includes lists of products that are registered for use on citrus, regardless of whether or not they are recommended for use. Written by Lauren M. Diepenbrock, Megan M. Dewdney, Tripti Vashisth, and Stephen H. Futch, and published by the Entomology and Nematology Department, May 2019.